2023
DOI: 10.1126/sciadv.adi7931
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale imaging of ytterbium ions in lead halide perovskites

Wen Xu,
Jiamu Liu,
Bin Dong
et al.

Abstract: Lanthanide-doped lead halide perovskites have demonstrated great potential for photoelectric applications. However, there is a long-standing controversy about the existence of lanthanide ions, e.g., whether the doping of Ln 3+ is successful or not; the substituting sites of Ln 3+ in lead halide perovskites are unclear. We directly identify the doped Yb 3+ in CsPbCl 3 perovskites by using the state-of-the-art transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…Since the Bi 3+ radius is larger than the Zn 2+ radius and some of the bismuth ions are doped into the Cs 2 ZnCl 4 NCs lattice to replace the zinc ions, this results in a slight expansion of the lattice, which also indicates the successful doping of Bi 3+ into the nanocrystalline lattice. 30–33 Additionally, the diffraction peak intensity of the nanocrystals gradually decreases and the peak broadens with further increase in Bi 3+ doping concentration. The diffraction peaks of nanocrystals with 10% and 20% doping concentrations show the most pronounced changes, with a sharp decrease in peak intensity and significant peak broadening.…”
Section: Resultsmentioning
confidence: 99%
“…Since the Bi 3+ radius is larger than the Zn 2+ radius and some of the bismuth ions are doped into the Cs 2 ZnCl 4 NCs lattice to replace the zinc ions, this results in a slight expansion of the lattice, which also indicates the successful doping of Bi 3+ into the nanocrystalline lattice. 30–33 Additionally, the diffraction peak intensity of the nanocrystals gradually decreases and the peak broadens with further increase in Bi 3+ doping concentration. The diffraction peaks of nanocrystals with 10% and 20% doping concentrations show the most pronounced changes, with a sharp decrease in peak intensity and significant peak broadening.…”
Section: Resultsmentioning
confidence: 99%
“…A similar conclusion was recently made for the incorporation of ytterbium ions in CsPbCl 3 nanoparticles. 15 According to Milstein et al , 4 two Yb +3 ions together with Pb 2+ vacancies form electrically neutral trap states and enable delivery of perovskite exciton energy simultaneously to two ytterbium ions.…”
Section: Resultsmentioning
confidence: 99%
“…3 Xu et al have recently reported strong evidence that Yb 3+ ions can be incorporated into CsPbCl 3 nanoparticles substituting Pb 2+ or occupying interstitial sites. 15…”
Section: Introductionmentioning
confidence: 99%
“…However, the high cost of rare earth elements may limit their commercialization. [14][15][16] To overcome these limitations, researchers have proposed the development of scintillators based on zero-dimensional (0D) or one-dimensional (1D) lead-free copper(I) halides. [17][18][19] These environmentally friendly crystals offer significant advantages, including their nonradioactive nature, better stability, low cost, and high-efficient self-trapped exciton (STE) emission with large Stokes shifts.…”
Section: Introductionmentioning
confidence: 99%